Bibliometric Analysis of Global Trends in Remimazolam-Related Research Over the Past 15 Years: Compared with Propofol - Hu X; Wang B; Hu L; Han D; Wu J (Dove Medical Press, 2023)
Xinyue Hu, Beibei Wang, Li Hu, Dong Han, Jing Wu Department of Anesthesiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of ChinaCorrespondence: Jing Wu, Department of Anesthesiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, HB, 430022, People's Republic of China, Tel +86-27-85351618, Email drjingwu@hust.edu.cnPurpose: Although remimazolam is a popular novel anesthetic, there is a lack of data in the literature about current and future trends. Therefore, the aim of this study was to explore emerging trends and potential hotspots of remimazolam research over the past 15 years through bibliometric methods.Methods: Relevant articles on remimazolam published from 2007 to 2022 and propofol from 1997 to 2001 were retrieved from the Web of Science Core Collection database. Data were collected using Microsoft Excel and graphs were generated with the Bibliometrix package in R software. Visual bibliometric maps were created using VOS viewer and CiteSpace software.Results: In total, 184 articles were included for analysis. Remimazolam-related research tended to increase, especially from 2020 to 2022. China produced the most publications (327), whereas the USA dominated in quality (h-index = 16). Among institutions, PAION Deutschland GmbH produced the most articles (Np = 21). Similar to initial research and development of propofol, the hotspots of remimazolam research have extended beyond pharmacokinetics and pharmacodynamics to adverse reactions, clinical scenarios, specific populations, and compatible regimens, as confirmed by high numbers of common references and keywords.Conclusion: Remimazolam research has developed rapidly over the past two years. Remimazolam can achieve faster onset and recovery, and more stable hemodynamics than midazolam or propofol, enabling gradual piloting of applications from endoscopy and general anesthesia to sedation of critical care patients; foreseeing specific population (patients with hepatic or renal impairment and reduced cardiovascular reserve, the elderly, and children) through compatible anesthetics regimens to more optimal and safe. Future studies of remimazolam are likely to include adverse reactions, effects on different organ systems, and identification of monitoring indicators.Keywords: remimazolam, CNS 7056, bibliometric analysis, applications, specific population, research trends